About the minimum time transference in a fractional differential equation - Barbanti, Luciano [UNESP]; Damasceno, Berenice Camargo [UNESP] (Amer Inst Physics, 2014)
The use of fractional calculus when modeling phenomena allows new queries concerning the deepest parts of the physical laws involved in. Here we will be dealing with an apparent paradox in which the time of transference from zero in a system with fractional derivatives can be strictly shortened relatively to the minimal time transference done in an equivalent system in the frame of the entire derivatives.